The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/spc3.12412
|View full text |Cite
|
Sign up to set email alerts
|

Psychological momentum: The phenomenology of goal pursuit

Abstract: Psychological momentum (PM) is thought to be a force that influences judgment, emotion, and performance. Based on a review of the extant literature, we elucidate two distinct approaches that researchers have adopted in their study of PM: the input‐centered approach and the output‐centered approach. Consistent with the input‐centered approach, we conceptualize PM as a process whereby temporal and contextual PM‐like stimuli (i.e., perceptual velocity, perceptual mass, perceptual historicity, and perceptually int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…Furthermore, within the context of status momentum, Pettit et al27 found that participants who were exposed to an ascending rank scenario subsequently developed enhanced perceptions of feelings of acceptance from others than those who were exposed to a descending rank scenario, even though the final rank itself was held constant. These studies indicate that simulations allow people to “preview” events and “pre-feel” the pleasures and pains that those events will produce, thus affecting judgments and decision-making 28. Therefore, we can speculate that in the context of shopping, contrary to the effect of upward simulation, the downward simulation will elicit negative emotions, thereby inhibiting impulse buying.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, within the context of status momentum, Pettit et al27 found that participants who were exposed to an ascending rank scenario subsequently developed enhanced perceptions of feelings of acceptance from others than those who were exposed to a descending rank scenario, even though the final rank itself was held constant. These studies indicate that simulations allow people to “preview” events and “pre-feel” the pleasures and pains that those events will produce, thus affecting judgments and decision-making 28. Therefore, we can speculate that in the context of shopping, contrary to the effect of upward simulation, the downward simulation will elicit negative emotions, thereby inhibiting impulse buying.…”
Section: Introductionmentioning
confidence: 99%
“…A social psychology literature associates the perception of moving toward a desired goal with the phenomenon of psychological momentum, which reflects a sort of psychological force that enhances positive self-perceptions (e.g., self-efficacy) and engagement in the task or activity (e.g., Briki and Markman 2018;Markman and Guenther 2007). Hence, our study suggests that conservative values (e.g., abnegation, responsibility) can enhance SWB by precipitating experiences of psychological momentum.…”
Section: Discussionmentioning
confidence: 75%
“…We examined the mediating effect of dispositional self-control because Schlenker et al (2012) regarded this variable as "a core element" of positive adjustment in conservatives. As for dispositional flow and goal progress, we investigated these two constructs because they are reputed to play a non-negligible role in the self-regulation of cognitions, emotions and behaviors, and are known to be linked to personal agency (e.g., self-efficacy) (see Briki and Markman 2018;Markman and Guenther 2007). We also examined dispositional neurotic self-attentiveness (corresponding to dispositional rumination) because Napier and Jost (2008) assumed that "liberals might become less satisfied with their current situation because of the deleterious effects of rumination) (p. 565).…”
mentioning
confidence: 99%
“…PM is based on the notion that future behavior is more likely to be consistent with past behavior, because this earlier behavior has unleashed a psychological force or impulse that effects performance. Briki and Markman [ 33 ] defined PM as the “cognitive, emotional, physiological, and behavioral responses to perceptions of progress moving either toward or away from a goal state” ([ 33 ], p. 2) and construed PM as the phenomenological experience of goal pursuit. PM theory proposes that the velocity of progress, conceptualized as the direction and magnitude of a change towards a certain goal [ 34 ], leads to positive or negative momentum.…”
Section: Introductionmentioning
confidence: 99%